Central China Orogen along the Silk Road (Part 2): Mineral deposits, hydrocarbons, geohazards, and environments. (30th March 2018) - Li, Sanzhong; Suo, Yanhui; Yu, Shengyao; Li, Rongxi; Yang, Gaoxue; Somerville, Ian
Abstract : This special issue (Volume 2) belongs to the special issues on Central China Orogen along the Silk Road. We selected 35 papers to focus on the mineral deposits, hydrocarbons, geohazards, and environments along the Central China Orogen of the Silk Road. We hope that these papers will highlight more research along the Silk Road to promote the construction and development of the Road and Belt.